2015
DOI: 10.1111/jdi.12344
|View full text |Cite
|
Sign up to set email alerts
|

Simple risk score to detect rural Asian Indian (Bangladeshi) adults at high risk for type 2 diabetes

Abstract: Aims/IntroductionTo develop and evaluate a simple, non-invasive, diabetes risk score for detecting individuals at high risk for type 2 diabetes in rural Bangladesh.Materials and MethodsData from 2,293 randomly selected individuals aged ≥20 years from a cross-sectional study in a rural community of Bangladesh (2009 Chandra Rural Study) was used for model development. The validity of the model was assessed in another rural cross-sectional study (2009 Thakurgaon Rural Study). The logistic regression model used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Indeed, the incidence and risk factors of T2DM in a population determine the suitability of a risk score. Some scores developed in a particular population often do not perform well in other populations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the incidence and risk factors of T2DM in a population determine the suitability of a risk score. Some scores developed in a particular population often do not perform well in other populations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…28,29 This study also revealed that diabetes was more likely (3.1 times) to develop amongst overweight and obese compared to that of underweight young adults. However, in the current study in regards to Waist-Hip ratio, no significant difference of central obese was found between DM, IGT and normal glycaemic status.…”
Section: Discussionmentioning
confidence: 68%
“…28 But, a recent study conducted in Bangladesh revealed that males were more (1.5 times) likely to develop diabetes. 29 Further, a hospital-based study in Bangladesh also revealed males (1.39 times) were more likely to develop diabetes compared to that of the females.…”
Section: Discussionmentioning
confidence: 99%
“…All studies included participants from all genders and social classes Rathnayake-2020 which was done in post-menopausal women(16). Majority of studies did not specify the theory/model/framework used to build the tools while 5 studies(17)(18)(19)(20)(21) used regression models to develop the tools. The studies characteristics are summarized in table-1 below.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies reported on 11 tools related to medical assessment in older adults. Four tools - MDRF-IDRS(24), Simple DRS(17), DRS-urban Indians(20), IDRS(25) were for risk scoring of diabetes by regression models using baseline population data. All tools reported moderate sensitivity (range: 62.2%-76.6%) and specificity (range: 59.9-73.7), excellent PPV of over 95% each but poor NPV of below 20%.…”
Section: Resultsmentioning
confidence: 99%